Are 12-lead ECG findings associated with the risk of cardiovascular events after ischemic stroke in young adults?. (2nd October 2016) - Pirinen, Jani; Putaala, Jukka; Aarnio, Karoliina; Aro, Aapo L.; Sinisalo, Juha; Kaste, Markku; Haapaniemi, Elena; Tatlisumak, Turgut; Lehto, Mika
Abstract: Introduction: Ischemic stroke (IS) in a young patient is a disaster and recurrent cardiovascular events could add further impairment. Identifying patients with high risk of such events is therefore important. The prognostic relevance of ECG for this population is unknown. Materials and methods: A total of 690 IS patients aged 15–49 years were included. A 12-lead ECG was obtained 1–14 d after the onset of stroke. We adjusted for demographic factors, comorbidities, and stroke characteristics, Cox regression models were used to identify independent ECG parameters associated with long-term risks of (1) any cardiovascular event, (2) cardiac events, and (3) recurrent stroke. Results: Median follow-up time was 8.8 years. About 26.4% of patients experienced a cardiovascular event, 14.5% had cardiac events, and 14.6% recurrent strokes. ECG parameters associated with recurrent cardiovascular events were bundle branch blocks, P-terminal force, left ventricular hypertrophy, and a broader QRS complex. Furthermore, more leftward P-wave axis, prolonged QTc, and P-wave duration >120 ms were associated with increased risks of cardiac events. No ECG parameters were independently associated with recurrent stroke. Conclusion: A 12-lead ECG can be used for risk prediction of cardiovascular events but not for recurrent stroke in young IS patients. KEY MESSAGES: ECG is an easy, inexpensive, and useful tool for identifying young ischemic stroke patients with a high risk for recurrent cardiovascular events and it has a statistically significant association with these events even after adjusting for confounding factors. Bundle branch blocks, P-terminal force, broader QRS complex, LVH according to Cornell voltage duration criteria, more leftward P-wave axis, prolonged QTc, and P-wave duration >120 ms are predictors for future cardiovascular or cardiac events in these patients. No ECG parameters were independently associated with recurrent stroke.